Commercial networks between the Byzantine Empire and Europe, including the British Isles - Ene Draghici-Vasilescu, E (IOSR Journals, 2022)
In the literature concerning Byzantium usually the historical phenomena are analysed as they took place along the Eastern-Western axis of its territory. What my paper proposes is an alternative to this approach. Because of the need to circulate goods between the Mediterranean and the North Sea, roads were constructed to connect the two, and along these both merchandises (textiles, metal objects, etc.) and cultural items as manuscripts, ivory for book covers, pigments for painting, etc. were transported. The same thoroughfares and points of connection within a large network were used for religious purposes and by the military; the latter was evident especially during crusades, and that fact is well documented. I will bring testimonies to make a strong argument that the division ‘North-South’ within the Empire was as important as that ‘East-West’.